The question of national identity in Notas de Arte and Miltín 1934, by Juan Emar (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
The literary avant-garde represents a cosmopolitan trend in Latin America, but in many writers there is also an important concern about national identity. This article shows how Juan Emar, a cosmopolitan Chilean author, takes part in the discussion about national art during the 1920’s and 1930’s. If artistic activity carries a national identity, he proposes, in his Notas de Arte, it appears in representation as a process, not as an object. The novel Miltín 1934 (1935) will put into practice this rule by showing the lapse of 19th century national pact and the author’s reluctance to committo a new nationality, collective and popular, that will be constructed throughout the 20th century.
Keywords: Nation; literary avant-garde; Juan Emar; Chilean narrative